International Dialogue: Our Experience in a Family Therapy Program - Mcdowell, Teresa; Fang, Shi-Ruei; Griggs, Julie; Speirs, Karl; Perumbilly, Sebastian; Kublay, Aliye Ebru (Journal of Systemic Therapies, 2006)
In this paper, we report our experiences as part of an international dialogue group within a U.S. family therapy training program. We describe the dialogue group and share the outcomes of our work together, including our understandings of how global relations, social positions, and personal/cultural characteristics influence our interactions within local contexts. We discuss how participation increased our international awareness and competence, offering two illustrations of how the group helped participants consider family therapy practice and research from a global perspective. Finally, we share the subjective experiences of student group members from the Southern United States, India, Turkey, and South Africa as testimony to the value of cross-national dialogue and to making space for affirming the unique journeys of international learners.
Keywords: dept.mft; peer-reviewed

Viewing the Asian American Experience Through a Culturally Centered Research Lens: Do Scholarship in Family Science and Related Disciplines Fall Short? - Fang, Shi-Ruei Sherry; McDowell, Teresa; Goldfarb, Katia P.; MacDonald, Angella; Perumbilly, Seb; Gonzalez-Kruger, Gloria E. (Marriage & Family Review, 2008)
To better understand and serve Asian-Americans, it is imperative for the family science related fields to take a leadership role in providing in-depth insight into Asian-American families. In this article we report a descriptive analysis of articles published in prominent family-based journals over a 14-year period (1992–2006) relative to their attention to Asian-American families. This study examines the types of research conducted and the knowledge that has been generated about Asian-American families. It also provides a framework for considering future culturally centered research with this population.
_eprint: https://doi.org/10.1080/01494920802185058
Keywords: Asian-Americans; culturally sensitive research approaches; dept.mft; family science; peer-reviewed

Working with Asian Indian American Families: A Delphi Study - Khanna, Anchal; Mcdowell, Teresa; Perumbilly, Sebastian; Titus, Gayatri (Journal of Systemic Therapies, 2009)
In this paper, we contribute to an agenda of developing culturally informed practices, centering specifically on working with Asian Indian and Asian Indian American families. We report the results of a modified Delphi study in which we asked advanced members of the counseling field who are of Asian Indian origin to share their insight relative to family therapy with those who identify as Asian Indian or Asian Indian American in the U.S. Panelists offered a multitude of recommendations, including the importance of: careful assessment that acknowledges within group similarities and differences; attention to extended family ties and intergenerational dynamics; understanding issues of immigration, acculturation, and discrimination; and development of treatment approaches that are congruent with Asian Indian cultural values, beliefs, and practices.
Keywords: dept.mft; peer-reviewed

The Measurement of Outcome Variables in Couple and Family Therapy Research - Sanderson, Jessica; Kosutic, Iva; Garcia, Marisol; Melendez, Tatiana; Donoghue, Jamie; Perumbilly, Sebastian; Franzen, Caroline; Anderson, Stephen (The American Journal of Family Therapy, 2009)
Measurement constitutes a central issue in determining effectiveness of couple and family therapy (CFT). A review of 274 CFT outcome studies published in 25 mental health journals between 1990 and 2005 is presented. Goals of this review were to (1) provide a broad, empirically based overview of CFT outcome research, (2) examine measurement of treatment outcomes, and (3) appraise reporting practices. Findings indicate that a wide range of instruments continue to be used in CFT outcome research, although a foundation for a more integrated and coherent assessment battery has been established. Implications for the field are discussed.
_eprint: https://doi.org/10.1080/01926180802405935
Keywords: dept.mft; peer-reviewed

Supervised Visitation. - Lynch, Barbara (2000)
Keywords: dept.mft; faculty_collection; sabbatical_report

Normal Madness, Murder and Mayhem - Lynch, J. Edward (Xlibris Corp, 2008)
Keywords: dept.mft; faculty_collection

Nurturing Queer Youth: Family Therapy Transformed - Stone Fish, Linda; Harvey, Rebecca G. (Norton, 2005)
Keywords: Case studies; Case studies; Gay youth; Counseling of; Bisexual youth; Counseling of; Family psychotherapy; Family relationships; Gay youth; dept.mft; faculty_collection

North Star Facilitator's Manual - Manke, Nancy; Matheny, Karla; De Barbieri, Patricia (s.n., 2004)
A program for school-age girls designed to promote social and emotional learning, to enhance resiliency, improve self confidence and aid in the prevention of future problems such as eating disorders, drug abuse and poor academic performance. - p. [1]
Keywords: Self-esteem in women; Study and teaching; Study and teaching; Self-esteem in children; dept.mft; faculty_collection

Undergraduates and intercultural communication competence: Creating a plan for performance - Madlock, A. (International Journal of Learning, 2009)
Some studies indicate that students develop intercultural communication competence through interaction in multicultural classrooms. However, what happens when classrooms are predominately homogenous and student exposure to other cultures is limited to media representations? It is not uncommon to find this situation still existing on some college campuses in the United States of America, where students have never come in contact with individuals different from themselves, beyond service industry workers, if any contact is made at all. The idea of establishing a significant relationship with someone culturally different is not given any thought. As an instructor of color how does one get students to move beyond their comfort zone and take action to meet individuals that are culturally different outside of the classroom? This paper describes the results of a textual analysis using grounded theory of student writing as they reflect on how to develop and implement effective communication strategies with individuals culturally and ethnically different from themselves outside of the classroom. The results of which might also be used to transform thinking about the diverse community surrounding the university and influence future decision-making on issues of social justice and human equality. © Common Ground, Annette Madlock.
Keywords: Grounded theory; Intercultural communication Competence; Multicultural classroom; Textual analysis; Undergraduates; dept.com; ⛔ No DOI found

Saladin and the truth of religion in Decameron I. 3 and X. 9 - Rhodes, J. (Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee, 2009)
Journal Abbreviation: Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee
Keywords: dept.eng

Essential skills in family therapy: From the first interview to termination - Lynch, BJ (American Journal of Family Therapy, 2000)
tex.unique-id: ISI:000086342500009
Keywords: dept.mft; ⛔ No DOI found